2005
DOI: 10.1007/s10620-005-2786-3
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Erythrocytes Distinguishes Fixed Cells/Tissues from Viable Cells/Tissues Following Microwave Coagulation Therapy

Abstract: Microwave coagulation therapy (MCT) has recently been applied to treat hepatic tumors. However, the histological changes in the liver following MCT have not been fully elucidated. A type of cell death known as microwave fixation has been reported in areas adjacent to the microwave irradiator electrodes, and these areas are without acid phosphatase (AcP) activity. Diagnosis of microwave-fixed tissue by hematoxylin and eosin (HE) staining is very difficult because morphology is well maintained for months. In an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Cytoplasmic content was well structured, with easily identifiable organelles ( Figure 10A). As previously described by Yamaguchi et al [20], erythrocytes within the white zone were destroyed, whereas those in surrounding tissue showed well maintained structure.…”
Section: Transmission Electron Microscopic Analysissupporting
confidence: 65%
“…Cytoplasmic content was well structured, with easily identifiable organelles ( Figure 10A). As previously described by Yamaguchi et al [20], erythrocytes within the white zone were destroyed, whereas those in surrounding tissue showed well maintained structure.…”
Section: Transmission Electron Microscopic Analysissupporting
confidence: 65%
“…19,20 In this study, 5 cases with HE stain showed noˆxation, but destruction of tumor cells. We excluded tumors with apparent central necrosis from our study.…”
Section: Discussionmentioning
confidence: 45%
“…A signiˆcant diŠerence among the 3 areas was found only with ADC values between Areas B and C. Water diŠusion might be aŠected by injury of the cell membrane caused by microwave coagulation. 20 In this study, ADC values were obtained from DWIs with 500-and 1000-s/mm 2 b values. Some studies of white matter of the brain have applied b values greater than 2000, 26,27 but high b values in body diŠusion for malignancies usually range from 800 to 1000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety margin is the most important factor for achieving the optimal treatment outcome [28][29][30]. To improve the accuracy of MCT, we developed a "Footprint" system [31].…”
Section: Discussionmentioning
confidence: 99%